MOLECULAR PATHOLOGY OF CANCER: UNDERSTANDING GENETIC AND EPIGENETIC ALTERATIONS - Dr Ameet Premchand (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Cancer arises from a combination of inherited and regulatory molecular alterations that contribute to tumor initiation, progression, and resistance to therapy. Determining how molecules alter needs to be fundamental for creating custom treatment approaches that are both precise and personalized. An overview of the most recently published work describing how variations in the genome and how gene expression control mechanisms are disrupted lead to malignancy is presented. Oncogenes, tumor suppression genes, DNA methylation, histone remodeling, and non-coding RNA are focused on. The review will also discuss the advanced methodologies to detect such changes, such as Next Generation Sequencing (NGS), Polymerase Chain Reaction (PCR), and liquid biopsy techniques. The united changes in cancer development that occur at the DNA level, changes in chromatin structure, and the modification of transcriptional regulation form a network of mutations. Tests on tyrosine kinase inhibitors adjunct with immune checkpoint blockers and agents for aberrant methylation therapy show positive results in clinical testing. One way to achieve this understanding will be to improve our understanding of the structural changes in DNA as well as the regulatory disruptions that accompany these changes. Decreasing them further is based on continual innovation in diagnostic tools and integrative treatment strategies in patient care.